Tingkat Stres Pelajar Sekolah Menengah Saat Pembelajaran Jarak Jauh Pada Masa Pandemi Covid-19 - Fidah Syadidurrahmah; Hany Fauzia Rahmah; Hoirun Nisa (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2022)
The COVID-19 pandemic that occurred in 2020 led to the implementation of the Distance Learning (PJJ) system for students in Indonesia. The learning system that changes suddenly can trigger stress levels in students. This study aims to determine the factors that influence the occurrence of stress in high school students during PJJ in Jabodetabek. This study used a cross sectional study design and was conducted in October – November 2020. Sampling used a voluntary sampling technique. Junior and senior high school students in Jakarta, Bogor, Depok, Tangerang, and Bekasi (n=414) participated in this study. Data was collected by filling out online questionnaires. Multivariate analysis was performed by logistic regression. During PJJ, 50.5% of students experienced severe stress. The results of the multivariate analysis showed that female students (OR=2.444, 95% CI: 1.526 – 3.913); difficulty in accessing learning (OR= 4.244, 95% CI: 2.666 – 6.756); and poor level of understanding of the material (OR= 2.657, 95% CI 1.541 – 4.582) affected the stress level of students during PJJ. We concluded that severe stress during PJJ was quite high in middle school participants. Female students, difficulty of access, and level of understanding of the material were significantly associated withthe stress level of participants. The variable most related to student’s stress was difficulty in accessing learning material. It is better if the education provider ensure that every student easily to access learning, evaluates the PJJ method regularly, improves students; stress management skills, creates a supportive educational environment, and pays attention to the learning media used. Abstrak Pandemi COVID-19 yang terjadi pada tahun 2020 menyebabkan diberlakukannya sistem Pembelajaran Jarak Jauh (PJJ) pada pelajar di Indonesia. Sistem pembelajaran yang berubah secara tiba-tiba dapat memicu tingkat stres pada pelajar. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan stres pada pelajar sekolah menengah selama PJJ di Jabodetabek. Studi ini menggunakan desain cross sectional dan dilakukan pada bulan Oktober – November 2020. Teknik voluntary sampling digunakan dalam pemilihanresponden. Pelajar Sekolah Menengah Pertama dan Atas di Jakarta, Bogor, Depok, Tangerang, dan Bekasi (n=414) berpartisipasi dalam penelitian ini. Pengumpulan data dilakukan dengan pengisian kuesioner secara online. Analisis multivariat dilakukan dengan regresi logistik. Selama PJJ, 50,5% pelajar mengalami stres berat. Hasil analisis multivariat menunjukkan pelajar perempuan (OR=2,444, 95% CI: 1,526-3,913); kesulitan dalam mengakses pembelajaran (OR= 4,244, 95% CI: 2,666-6,756); dan tingkat pemahaman materi yang kurang(OR= 2,657, 95% CI: 1,541-4,582) mempengaruhi tingkat stres pada pelajar selama PJJ. Kami menyimpulkan bahwa stres berat saat PJJ cukup tinggi pada responden pelajar menengah. Pelajar perempuan, kesulitan akses, berhubungan dengan stress pelajar adalah kesulitan dalam mengakses pembelajaran. Sebaiknya pihak penyelenggara pendidikan memastikan setiap pelajar mudah mengakses pembelajaran, mengevaluasi metode PJJ secara berkala, meningkatkan keterampilan manajemen stres siswa, menciptakan lingkungan pendidikan yang mendukung, dan memperhatikan media pembelajaran yang digunakan.